Establishment of five new genera in the family Geminiviridae: Citlodavirus, Maldovirus, Mulcrilevirus, Opunvirus, and Topilevirus - Roumagnac, Philippe; Lett, Jean-Michel; Fiallo-Olivé, Elvira; Navas-Castillo, Jesús; Zerbini, F. Murilo; Martin, Darren P.; Varsani, Arvind (Archives of virology, 2022)
Geminiviruses are plant-infecting, circular single-stranded DNA viruses that have a geminate virion morphology. These viruses infect both cultivated and non-cultivated monocotyledonous and dicotyledonous plants and have a wide geographical distribution. Nine genera had been established within the family Geminiviridae ( Becurtovirus, Begomovirus , Capulavirus , Curtovirus , Eragrovirus , Grablovirus, Mastrevirus , Topocuvirus , and Turncurtovirus ) as of 2020. In the last decade, metagenomics approaches have facilitated the discovery and identification of many novel viruses, among them numerous highly divergent geminiviruses. Here, we report the establishment of five new genera in the family Geminiviridae ( Citlodavirus, Maldovirus, Mulcrilevirus, Opunvirus , and Topilevirus ) to formally classify twelve new, divergent geminiviruses.